The Effect of The Syllabic System In Facilitating The Pronunciation of The Word An Analytical Study (Journal of the College of Basic Education, 2025)
The research addressed the importance of the syllabic system in facilitating the pronunciation of the word, especially if the word has many letters, by forming a series of linguistic sounds according to its division. Accordingly, it has a great impact in terms of alleviation and avoiding heaviness. The research was divided into an introduction and two sections, followed by a conclusion and a list of research sources, as followsThe first topic: The concept of the syllable in Arabic. 1-2-The effect of the syllabic system in facilitating the performance of word pronunciation.